PEMODELAN ADD-DROP MICRORING RESONATOR DALAM MEMPEROLEH HARGA KECEPATAN DATA DAN DAYA UNTUK SISTEM KOMUNIKASI SERAT OPTIK - ', Hotmariani; ', Saktioto; Irawan, Dedi (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Add-drop microring resonator is designed by using Single Mode Fiber (SMF) with the wavelength range from 1.30 to 1.35 micrometer, clutch coeficient varied with the value of 0.25/mm, 0.3/mm, 0.5/mm and 0.7/mm. The research is to obtain the magnification power and baud rate using Matlab R2012B and calculation of physical parameter characterizing microring resonator. The result obtained in this study shows that the value of power changes 0.77263 dB, 0.0016 dB, 0.0124 dB and 0.0475 dB and the value of baud rate is0.91548 nm, 1.3183 nm, 3.662 nm dan 7.1774 nm respectively. The results show that the Free Spectral Range (FSR) is unchanged, Full Width Half Maximum (FWHM) is increasing for coupling coeficient of 0.7 /mm, while Finesse and Quality Factor have the largest value in the coupling coeficient of 0.25 /mm.